2014
DOI: 10.4315/0362-028x.jfp-14-185
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Four Fusarium Mycotoxins, Deoxynivalenol, Zearalenone, T-2 Toxin, and HT-2 Toxin, in Wheat, Barley, and Japanese Retail Food

Abstract: A survey of the contamination of wheat, barley, and Japanese retail food by four Fusarium mycotoxins, deoxynivalenol (DON), zearalenone (ZEN), T-2 toxin (T-2), and HT-2 toxin (HT-2), was performed between 2010 and 2012. A method for the simultaneous determination of the four mycotoxins by liquid chromatography-tandem mass spectrometry was validated by a small-scale interlaboratory study using two spiked wheat samples (DON was spiked at 20 and 100 μg/kg and ZEN, T-2, and HT-2 at 6 and 20 μg/kg in the respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The European Union (EU) has recognized permissible limits for ZEA in unprocessed cereals as 100 μg/kg excluding maize and in unprocessed maize was 350 μg/kg ( European Commission, 2007 ). However, reports of Pleadin et al (2012) revealed that maize grains were contaminated with high levels of 5.11 mg/kg ZEA and also Yoshinari et al (2014) reported that Job’s tears products of cereals have been found as 3.1 to 5.9 μg/kg of ZEA. These reports, further warns that there is an immediate need to develop a cost-effective bio-control strategy for successive mitigation of F. graminearum and ZEA contamination in food grains intended for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The European Union (EU) has recognized permissible limits for ZEA in unprocessed cereals as 100 μg/kg excluding maize and in unprocessed maize was 350 μg/kg ( European Commission, 2007 ). However, reports of Pleadin et al (2012) revealed that maize grains were contaminated with high levels of 5.11 mg/kg ZEA and also Yoshinari et al (2014) reported that Job’s tears products of cereals have been found as 3.1 to 5.9 μg/kg of ZEA. These reports, further warns that there is an immediate need to develop a cost-effective bio-control strategy for successive mitigation of F. graminearum and ZEA contamination in food grains intended for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…(Streit et al, ). Although the contamination level of T‐2 toxin is relatively lower than DON worldwide, it is still very common in many areas (Bhat & Reddy, ; EFSA, ; Pascale et al, ; Pinotti et al, ; Tutelyan et al, ; Yoshinari et al, ). T‐2 toxin is also a non‐negligible highly toxic mycotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…T‐2 toxin and deoxynivalenol (DON) are representatives of type A and type B trichothecenes, respectively, produced on diverse cereal grains, such as wheat, barley, oats and corn, by various fungi species such as Fusarium . The contamination by DON is reported as one of the most prevalent mycotoxins particularly in the Americas, Europe, Africa and Asia, becoming an important global issue of food safety (Bhat & Reddy, ; EFSA, ; Herrera, Anadón, Iqbal, Bailly, & Ariño, ; Knutsen et al, ; Pinotti, Ottoboni, Giromini, Dell Orto, & Cheli, ; Rodrigues & Naehrer, ; Rodríguez‐Carrasco, Fattore, Albrizio, Berrada, & Mañes, ; Streit, Naehrer, Rodrigues, & Schatzmayr, ; Yoshinari et al, ). In a scientific report by the European Food Safety Authority (EFSA), DON was found in 44.6%, 43.5% and 75.2% of unprocessed grains of undefined end‐use, food and feed samples respectively, collected by 21 European countries between 2007 and 2012 (EFSA, ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of trichothecene mycotoxins in agricultural products have been extensively researched. Our group performed a survey of the contamination of cereals and processed cereal-based foods by deoxynivalenol (DON), a type B trichothecene, and two type A trichothecene mycotoxins, T-2 toxin and HT-2 toxin, between 2010 and 2012 [ 2 ]. These trichothecene mycotoxins were detected in a variety of foods including wheat, barley, Job’s tears products, beer, corn flour and azuki bean.…”
Section: Introductionmentioning
confidence: 99%